First protection-free protocol for synthesis of 1-deoxy sugars through glycosyl dithiocarbamate intermediates. Issue 37 (12th September 2018) - Li, Gefei; Noguchi, Masato; Nakamura, Kensuke; Hayasaka, Ryohei; Tanaka, Yuuki; Shoda, Shin-ichiro
Graphical abstract: Highlights: Unprotected glycosyl dithiocarbamates as a useful intermediate for 1-deoxy sugar synthesis. No protecting-groups are needed to prepare 1-deoxy sugars. The 1-deoxy sugars help to elucidate the role of carbohydrates in metabolic cycles. Abstract: A practical two-step synthetic process for 1-deoxy sugars has been established. The process consists of the direct introduction of a dimethyldithiocarbamate group into the anomeric center of unprotected sugars and subsequent hydrogenation in the AIBN-H3 PO2 -NaHCO3 system. No protecting groups are needed to synthesize 1-deoxy monosaccharides and 1-deoxy disaccharides.